2018
DOI: 10.3389/fmicb.2018.01764
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Biological Activity of the Antimicrobial Lasso Peptide Microcin J25 Under Gastrointestinal Tract Conditions

Abstract: The bacteriocin microcin J25 (MccJ25) inhibits the growth of Gram-negative pathogens including Salmonella and Shigella species, and Escherichia coli. This 21-amino acid peptide has remarkable stability to heat and extreme pH values and resistance to many proteases, thanks to a characteristic lasso structure. In this study, we used the dynamic simulator TIM-1 as gastro-intestinal tract model to evaluate the stability and antibacterial activity of MccJ25 during passage through the proximal portion of the human g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
3
49
0
Order By: Relevance
“…Previously, our group described the degradome of MccJ25 in conditions mimicking the upper portion of the human gastrointestinal tract (i.e., stomach, duodenum, and ileon), which can be obtained using a dynamic simulator model (TIM-1). This study showed high stability of MccJ25 in the stomach and partial degradation by the enzymes encountered in the duodenum (Naimi et al, 2018). However, nothing is known about the stability and activity of MccJ25 in the colon and particularly in the proximal colon, a major site of salmonellosis in pigs.…”
Section: Introductionmentioning
confidence: 67%
“…Previously, our group described the degradome of MccJ25 in conditions mimicking the upper portion of the human gastrointestinal tract (i.e., stomach, duodenum, and ileon), which can be obtained using a dynamic simulator model (TIM-1). This study showed high stability of MccJ25 in the stomach and partial degradation by the enzymes encountered in the duodenum (Naimi et al, 2018). However, nothing is known about the stability and activity of MccJ25 in the colon and particularly in the proximal colon, a major site of salmonellosis in pigs.…”
Section: Introductionmentioning
confidence: 67%
“…In that way, the ability of microcin J25 to compete the pathogen Salmonella in the human or animal gut conditions, as well as its stability in the different GI tract compartments, were examined using gut simulators. The degradome of microcin J25 was examined in both dynamic (TIM1 dynamic simulator) and static models of digestion, using antibacterial assays, LC-MS/MS, and molecular networking analysis (116). The stability and activity are quite good in the stomach acidic conditions, but the lassoed microcin partly degrades in the compartment mimicking the duodenum conditions, in particular upon the action of elastase, one of the main enzymes in this GI compartment, showing that protection of the microcin will be required for further applications.…”
Section: Ripp-mediated Competition Mechanismsmentioning
confidence: 99%
“…The former was derived from the AMPA antimicrobial peptide predictor [10,11], while the latter was quantified with respect to the peptides' affinity to endogenous proteases. Yet, the amount of cleavage recognition patterns in a given peptide sequence is only one factor in a more complex scheme that determines its actual decay rate reflecting the differential stability of peptides with different amino acid composition and different biological behaviours [37][38][39]. In order to approximate a more accurate estimation, we also incorporated HLP [19] in our ranking, a peptide half-life prediction model trained on peptide decay data from crude intestine extracts.…”
Section: Discussionmentioning
confidence: 99%